Hubungan Antara Faktor Predisposisi dengan Perilaku Pemakaian Kondom Untuk Mencegah IMS di Wilayah Kerja UPTD Puskesmas Sangkrah Kota Surakarta - Budiarti, Amina; , Badar Kirwono, SKM, M.Kes; , Anisa Catur Wijayanti, SKM., M.Epid (2015)
STI prevention consists of ABC (abstinence, Befaithfull, Condom). STI prevention is not maximized cause STI cases continue to occur. Condom use is not maximized STI prevention in the community. The purpose of this study was to determine the relationship of condom use behaviors predisposing factors. This study was an observational analytic study with cross sectional approach. Number of samples 98 samples consisting of Women of Fertile Age which married.Using chi-square analysis for bivariate analysis and logistic regression for multivariate analysis. Bivariate analysis of the test results obtained for the relationship between knowledge and condom use (p-value 0.003) POR 1.511 (95% CI; 1.225 to 1.864), attitude to condom use (p-value 0.001) POR 1.557 (95% CI; 1.237 to 1.960 ), and perceptions with condom use (p-value 0.000). POR 2.080 (95% CI; 1.550 to 2.791). While the level of education has no connection with the behavior of condom use (p-value 0.404).In the multivariate analysis result, the perception of the factors that most influence on the behavior of condom use.Exp (B) 39.657 (95% CI; 3.976 to 395.536) means that the perception of condoms have the effect of 39.657 times in the behavior of condom use duringsexual intercourse.